Issues Affecting the Loco‐regional and Systemic Management of Patients with Invasive Lobular Carcinoma of the Breast. Issue 1 (January 2016) - Jacobs, Carmel; Clemons, Mark; Addison, Christina; Robertson, Susan; Arnaout, Angel
Abstract: Invasive lobular carcinoma (ILC) of the breast is the second most common type of invasive breast carcinoma accounting for 8–14% of all breast cancers. Traditional management of ILC has followed similar paradigms as that for invasive ductal carcinoma (IDC). However, ILC represents a pathologically, clinically and biologically unique variant of breast cancer with particular management challenges. These challenges are seen in both the loco‐regional management of ILC; where ILC tumors tend to avoid detection and hence present as more clinically advanced and surgically challenging carcinomas, and the systemic management with a unique response pattern to standard systemic therapies. Because of these challenges, the outcome for patients with ILC has likely lagged behind the continued improvements seen in outcome for patients with IDC. Here, we discuss some of the unique challenges ILC presents and discuss possible management strategies to best overcome the difficulties in the loco‐regional and systemic management of patients with ILC.